Student Perceptions of Group Work and Group Formation Strategies - Bussberg, Nicholas W.; Taylor, Laura L. (Journal of statistics and data science education, 2025)
Group work is a common practice in statistics and data science courses. However, students in introductory courses often have a wide range of previous experience with group work. In this study, we examine the perceptions of introductory statistics students around group formation at a medium-sized liberal arts university. Group experiences were implemented in two ways. First, students rotated through assigned group seating throughout the semester to work in new teams on in-class work. Second, students completed two group projects. For the first group project, students were randomly assigned a team, and on the second project, students could choose between picking a team of students or being randomized into a team. Pre- and post-semester surveys were used to gather student perceptions around group work formation and to better understand perceived benefits of each method. Students also completed post-project reflections about their project experiences. Surveys and reflections indicated that students preferred working with others that they knew best, but respondents still identified benefits such as getting to know other classmates when working in randomly assigned teams. Responses also indicated the importance of work ethic (e.g., trusting partners, fair distribution of workload) regarding potential teammates for both randomized and self-selected groups.